Factors influencing green product purchase intention among Gen-Z Muslims - Saifudin, Saifudin; Hartiningsih, Sepia; Lukman, Najah; Hamdan, Haslenna (Asian Journal of Islamic Management (AJIM), 2025)
Purpose – This study aims to analyze the influence of online green product reviews, self-image congruence, attitude, subjective norms, and perceived behavioral control on the intention to purchase environmentally friendly products among Generation Z Muslims in Salatiga City, an area renowned for its environmental management achievements.Methodology – A quantitative research design was used, employing purposive sampling of 350 respondents aged 17 years and above. Data were collected through questionnaires and analyzed using structural equation modeling (SEM) with SmartPLS 3.2.9.Findings – The study found that online green product reviews, self-image congruence, attitude, and perceived behavioral control had a significant positive effect on the purchase intention of green products. However, subjective norms only showed a significant impact on product reviews, and not directly on purchase intention. The dominant factors influencing purchase intention are attitude and self-image congruence.Implications – The findings suggest that marketing strategies should focus on aligning product image with consumer identity, emphasizing attitude, and self-image congruence. Additionally, leveraging online reviews can serve as an effective tool for pro-environmental education and the promotion of green product purchases.Originality – This research provides valuable insights into the environmental awareness and consumption behavior of Generation Z Muslims in Salatiga City, contributing to the understanding of the factors influencing the intention to purchase environmentally friendly products, especially in emerging markets with strong environmental values.